2012
DOI: 10.1186/1741-7015-10-154
|View full text |Cite
|
Sign up to set email alerts
|

The impact of statins on psychological wellbeing: a systematic review and meta-analysis

Abstract: BackgroundCholesterol-lowering medications such as statins have anti-inflammatory and antioxidant properties, which may be beneficial for treating depression and improving mood. However, evidence regarding their effects remains inconsistent, with some studies reporting links to mood disturbances. We aimed to conduct a meta-analysis to determine the impact of statins on psychological wellbeing of individuals with or without hypercholesterolemia.MethodsArticles were identified using medical, health, psychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 33 publications
4
49
0
3
Order By: Relevance
“…Nor was there evidence for an adverse effect of statin therapy in a meta-analysis of randomized trials that assessed psychological outcomes. 267 …”
Section: Quality Of Life Related Measuresmentioning
confidence: 99%
“…Nor was there evidence for an adverse effect of statin therapy in a meta-analysis of randomized trials that assessed psychological outcomes. 267 …”
Section: Quality Of Life Related Measuresmentioning
confidence: 99%
“…Lowered blood pressure in psychopathology may be a consequence of shared risk factors, such as levels of neuropeptide Y, which is associated with suppressed parasympathetic activity and stress, depression and anxiety 45. The reason for the positive association between symptom severity and HDL‐C is unclear, particularly since HDL‐C has anti‐inflammatory properties 46 and recent evidence suggests that use of cholesterol improving medication is associated with improved mental health 47. Nevertheless, the findings are consistent with previous research demonstrating that depressive symptoms and suicidality are associated with lowered total cholesterol and higher HDL‐C,48, 49 although heterogeneity between studies is high and the effect is not always observed 50, 51.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs are thought to have a potential anti-depressive effect related to their anti-inflammatory properties [8,64]. A number of epidemiological studies show that statin use reduces depression risk [65,66], and the only randomized controlled trial to date suggests that lovastatin reduced symptoms of depression [67].…”
Section: Gaps and Required Improvements: New Treatmentsmentioning
confidence: 99%